Nanorrhinum roseiflorum (Scrophulariaceae), a new species from Dhofar, Southern Oman - Mosti, Stefano; Raffaelli, Mauro; Tardelli, Marcello (Webbia, 2008)
Nanorrhinum roseiflorum, characterized by pink flowers, a twiggy shrub habit and very small leaves, is described as a new species from Dhofar (Oman). it is distributed on the mountain rocky slopes of Jabal Qara, from Qaftwat to Wanat, at an altitude of 900–1150 m, and in the dry area of Wadi Andur, behind Jabal Samhan, at an altitude of 600 m.
Keywords: Botanique – Oman

Apocynaceae of Oman: Orbea nardii, sp. nov. and Pentatropis bentii, first finding - Raffaelli, Mauro; Mosti, Stefano; Tardelli, Marcello (Webbia, 2008)
Orbea nardii, a new species found in the mountains of Al Mughsayl (central Dhofar, Oman) is here described and compared with some other closely related species of Orbea. Moreover the presence of Orbea luntii in Dhofar is confirmed on the basis of its finding on the southern slope of Jabal Samham and, finally Pentatropis bentti, found in the mountains of Hasik, eastern Dhofar, is recorded for the first time.
Keywords: Botanique – Oman

Botanical and chemical characterization of frankincense resin from Dhofar - Ribechini, Erika; Raffaelli, Mauro; Colombini, Maria Perla (A port in Arabia between Rome and the Indian Ocean: 3rd C.BC-5th C.AD, 2008)
Keywords: Botanique – Oman

Scientific activity in Dhofar (2000 - 2004): botanical mission of Florence University - Raffaelli, Mauro; Tardelli, Marcello; Mosti, Stefano (A port in Arabia between Rome and the Indian Ocean: 3rd C.BC-5th C.AD, 2008)
Keywords: Botanique – Oman